The Oxford handbook of political ideologies - Freeden, Michael 1944- HerausgeberIn; Sargent, Lyman Tower 1940- HerausgeberIn; Stears, Marc HerausgeberIn; Sargent, Lyman Tower HerausgeberIn (Oxford University Press, 2015)
This Oxford Handbook will be the definitive study of political ideologies for years to come. The diversity of ideology studies is represented by a mixture of the range of theories that illuminate the field, combined with an appreciation of the changing complexity of concrete ideologies and the emergence of new ones.